Development of a Real-Time PCR Assay for the Detection of Donkey (Equus asinus) Meat in Meat Mixtures Treated under Different Processing Conditions - Kim, Mi-Ju; Suh, Seung-Man; Kim, Sung-Yeon; Qin, Pei; Kim, Hong-Rae; Kim, Hae-Yeong (Foods, 2020)
In this study, a donkey-specific primer pair and probe were designed from mitochondrial cytochrome b gene for the detection of raw donkey meat and different processed meat mixtures. The PCR product size for donkey DNA was 99 bp, and primer specificity was verified using 20 animal species. The limit of detection (LOD) was examined by serially diluting donkey DNA. Using real-time PCR, 0.001 ng of donkey DNA could be detected. In addition, binary meat mixtures with various percentages of donkey meat (0.001%, 0.01%, 0.1%, 1%, 10%, and 100%) in beef were analyzed to determine the sensitivity of this real-time PCR assay. At least 0.001% of donkey meat was detected in raw, boiled, roasted, dried, grinded, fried, and autoclaved meat mixtures. The developed real-time PCR method showed sufficient specificity and sensitivity in identification of donkey meat and could be a useful tool for the identification of donkey meat in processed products.